Criminal Liability for Doxing Perpetrators as a Form of CrimeCyber ​​Crime: A Study of Criminal Law in Indonesia - Anfathurrahman M. Thohari; Faisal Abdaud; Huzaiman (Ekasakti Journal of Law and Justice, 2025)
Cybercrime is a crime or illegal activity committed through electronic networks, particularly the internet, with cross-border characteristics and is difficult to trace. The rapid development of information technology has led to an increase in the complexity and quantity of cybercrimes, one of which is doxing, namely the act of spreading someone's personal data without permission through digital media that can cause material and immaterial losses to the victim. In the context of Indonesian law, doxing can be qualified as a crime based on laws and regulations governing information and electronic transactions and personal data protection. Law enforcement against perpetrators is carried out through the imposition of criminal sanctions in the form of imprisonment and/or fines as a form of accountability for the actions committed. This study aims to analyze the effectiveness of implementing criminal sanctions against doxing perpetrators in order to reduce the number of cybercrimes and prevent the repetition of criminal acts (recidivism). The research method used is normative juridical with a legislative and conceptual approach. The research results show that even though regulations are in place, the effectiveness of law enforcement still faces various obstacles, such as limited law enforcement capabilities, lack of public awareness, and faster technological developments than regulations. Therefore, it is necessary to optimize law enforcement, increase digital literacy, and update adaptive regulations to address doxing crimes more effectively.